Citizens’ experiences of enablers and barriers to obtaining digital citizenship - Gabriella Scaramuzzino; Kettil Nordesjö; Rickard Ulmestig (Journal of Comparative Social Work)
This article focuses on citizens’ experiences of enablers of- and barriers to obtaining digital citizenship. E-applications for social assistance are used as an exemplar. In Sweden, as in many countries, there is political pressure on welfare services to become more digitalized, and to offer different kinds of self-service technology such as e-applications. Even if the goals of implementing these technologies are to increase efficiency and transparency and offer faster services to citizens, there is a risk of expanding the ‘digital divide’. and making it more difficult to obtain one’s digital citizenship and gain access to social rights. This article draws on a qualitative interview study. and explores citizens’ experiences using e-applications in two Swedish municipal social assistance agencies. Results show that most citizens had positive experiences applying for social assistance online, but there were some potential barriers. There were also differences in experiences in the two municipal social assistance agencies. We discuss how the increased digitalization of welfare services seems to push towards a blend of digital and social rights. In this process, social workers play an important role in countering new types of inequalities that emerge in evolving social assistance organizations. The article identifies several areas that merit further research.